2022
DOI: 10.1111/jhn.13078
|View full text |Cite
|
Sign up to set email alerts
|

Baby‐led weaning: A thematic analysis of comments made by parents using online parenting forums

Abstract: Background: Baby-led weaning (BLW) centres on making the baby an active partner, rather than a passive recipient of complementary feeding. Key features of BLW include self-feeding foods in their natural form, eating with the rest of the family and consuming family foods. This differs from traditional weaning (TW) where parents initially spoon feed purees, alongside finger foods, before graduating to more textured food. Previous research, however, has suggested parents may not fully adhere to one weaning style.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…This could be because mothers practicing BLW may experience greater anxiety due to concerns about choking hazards, ensuring adequate nutrition, and the overall safety of allowing infants to self-feed [26]. For some, BLW felt like a natural transition that required little parental effort, but for others, it was a source of worry, anxiety, choking danger, and chaos [27]. However, these ndings oppose those of Arden & Abbott [28], who showed that mothers who followed the BLW method reported less anxiety during meals; they also expressed high levels of con dence in their babies' capacity to decide when, what, and how much food to eat.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because mothers practicing BLW may experience greater anxiety due to concerns about choking hazards, ensuring adequate nutrition, and the overall safety of allowing infants to self-feed [26]. For some, BLW felt like a natural transition that required little parental effort, but for others, it was a source of worry, anxiety, choking danger, and chaos [27]. However, these ndings oppose those of Arden & Abbott [28], who showed that mothers who followed the BLW method reported less anxiety during meals; they also expressed high levels of con dence in their babies' capacity to decide when, what, and how much food to eat.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the possibility that baby‐led infants consume eggs more frequently as they are viewed to be less fussy and more adventurous in their eating style and food acceptance 38–40 . At present there are no experimental studies testing food fussiness in infants by weaning style, and data rely on maternal report.…”
Section: Discussionmentioning
confidence: 99%
“…37 There is also the possibility that baby-led infants consume eggs more frequently as they are viewed to be less fussy and more adventurous in their eating style and food acceptance. [38][39][40] At present there are no experimental studies testing food fussiness in infants by weaning style, and data rely on maternal report. There was no difference in infant perceived enjoyment of eggs between those following a baby-led and spoon-fed approach, but potentially views of baby-led infants being receptive to a wider range of foods might affect whether parents choose to introduce foods like eggs to their infant.…”
Section: Whole Samplementioning
confidence: 99%
“…Durante la primera fase lo mejor es que los bebés se mantengan únicamente con lactancia o fórmula, así pues, los padres tendrán que esperar hasta que su hijo muestre signos de desarrollo de preparación para autoalimentarse lo cual se ve reflejado alrededor de los seis meses. (6) Cuando el bebé pasa de alimentarse solo de un líquido como es la leche a incrementar sólidos en su dieta, lo óptimo será facilitar los alimentos en piezas de fácil agarre. (7) En un estudio observacional realizado por Brown et al (22) , donde se analizaron a 1151 bebés con riesgo de arcadas y asfixia, los resultados de dicha investigación apuntaron que cerca de un 11,9 % del grupo que implementó la práctica del BLW presentó episodios de atragantamiento, en tanto que en un 11,6 % de niños alimentados con la técnica tradicional también presentaron el mismo problema, es decir no se refleja una gran diferencia entre las dos prácticas alimentarias.…”
Section: Introductionunclassified